Cell Therapy with Human Dermal Fibroblasts Enhances Intervertebral Disk Repair and Decreases Inflammation in the Rabbit Model. (December 2016) - Chee, Ana; Shi, Peng; Cha, Thomas; Kao, Ting-Hsien; Yang, Shu-Hua; Zhu, Jun; Chen, Ding; Zhang, Yejia; An, Howard S.
Study Design: Pilot study using the rabbit model. Objective: Low back pain is often associated with disk degeneration. Cell therapy for degenerating disks may promote tissue regeneration and repair. Human dermal fibroblasts, obtained from the patient's skin tissue or donated tissue, may be a promising cell therapy option for degenerating disks. The objective of these studies is to determine the effects of intradiscal transplantation of neonatal human dermal fibroblasts (nHDFs) on intervertebral disk (IVD) degeneration by measuring disk height, magnetic resonance imaging (MRI) signal intensity, gene expression, and collagen immunostaining. Methods: New Zealand white rabbits ( n = 16) received an annular puncture to induce disk degeneration and were treated with nHDFs or saline 4 weeks later. At 2 and 8 weeks post-treatment, X-ray and MRI images were obtained. IVDs were isolated and examined for changes in collagen staining and gene expression. Results: In the nHDF-treated group, there was a 10% increase in the disk height index after 8 weeks of treatment ( p ≤ 0.05), and there was no significant difference in the saline-treated group. When compared with the saline-treated disks, disks treated with nHDFs showed reduced expression of inflammatory markers, a higher ratio of collagen type II over collagen type I gene expression, and more intense immunohistochemical staining for both collagen types I and II. Conclusions: Human dermal fibroblast introduction into the disk reduced inflammation and promoted tissue rich in both type I and type II collagens. The results of this study suggest that nHDFs would be a feasible cell therapy option for disk degeneration.